2019
DOI: 10.1002/jcla.23017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hypercoagulability using thromboelastography predicts advanced status in renal cell carcinoma

Abstract: Background Thromboelastography (TEG) has been established as a sensitive method to assess the whole coagulation process. The aim of the study was to evaluate the diagnosis significance of TEG on hypercoagulability in patients suffering renal mass. Methods A total of 478 patients were diagnosed with renal tumor by histolopathologic examination and were assigned to three groups. Group A: 79 patients with benign renal tumor; Group B: 317 patients with renal cell carcinoma (RCC, Fuhrman grades I and II); Group C: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For example, the TEG parameters K time, Angle, and MA can predict the stage of lung cancer [ 31 ]. It has also been reported that advanced colorectal cancer usually exhibits hypercoagulable status, and MA is a potential effective biomarker for the identification of such cancer [ 32 ]. In addition, TEG parameters were significantly abnormal in patients with thyroid cancer; among these parameters, Angle, CI, and thrombodynamic potential index (TPI) had potential diagnostic utility for this type of cancer [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the TEG parameters K time, Angle, and MA can predict the stage of lung cancer [ 31 ]. It has also been reported that advanced colorectal cancer usually exhibits hypercoagulable status, and MA is a potential effective biomarker for the identification of such cancer [ 32 ]. In addition, TEG parameters were significantly abnormal in patients with thyroid cancer; among these parameters, Angle, CI, and thrombodynamic potential index (TPI) had potential diagnostic utility for this type of cancer [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to MTP-related blood product usage, TEG does not differ from conventional testing and ROTEM [40,41]. During trauma surgery involving the liver and spleen, interestingly, TEG guidance has demonstrated less as well as increased blood product usage but shorter surgery time [42,43]. With the success of TEG in assessing coagulopathic parameters in trauma patients, TEG has been investigated for detecting and reversing anticoagulants only with limited success, and conventional tests (e.g., PT, INR, PTT) that have shown better results comparatively have been recommended [44][45][46][47].…”
Section: Traumamentioning
confidence: 99%
“…50 A positive correlation was shown between fibrinogen and MA value and a particular MA value was helpful in detecting high-risk renal cell carcinoma. 51 In primary brain tumors where a hypercoagulable state is expected 24 hours postoperative, TEG was found to be useful perioperatively to identify coagulation abnormalities and guide treatment. 52…”
Section: Role Of Thromboelastography In Other Cancersmentioning
confidence: 99%